2022
DOI: 10.1177/10596011221098824
|View full text |Cite
|
Sign up to set email alerts
|

Do Multiple I-Deals in a Team Help or Hinder Team Outcomes? A Resource Scarcity Perspective

Abstract: Idiosyncratic deals (i-deals) are individualized employment arrangements negotiated and agreed upon by individual employees and their organization. This study addresses an emerging conundrum in i-deals research—whether the prevalence of i-deals in teams helps or hinders team outcomes. Because teams in which i-deals are prevalent receive more resources and status, they may be more cohesive and engage in more supportive behaviors. On the other hand, because i-deals differentiate among team members, teams in whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…Because I‐deals impart nonstandard rewards and privileges to recipients, I‐deals represent a valuable resource in organizations (Rousseau et al, 2016; Simosi et al, 2021), the availability or scarcity of which might influence how teams respond to I‐deals and firm performance. In addition, recent breakthroughs in the literature on teams (Vossaert et al, 2023) have revealed scenarios in which team‐related resources may improve organizational outcomes. Thus, the RBV gives a fine vantage point for examining the interaction between organizational and team‐level characteristics to forecast whether team I‐deals may contribute internationally to export SMEs.…”
Section: Introductionmentioning
confidence: 99%
“…Because I‐deals impart nonstandard rewards and privileges to recipients, I‐deals represent a valuable resource in organizations (Rousseau et al, 2016; Simosi et al, 2021), the availability or scarcity of which might influence how teams respond to I‐deals and firm performance. In addition, recent breakthroughs in the literature on teams (Vossaert et al, 2023) have revealed scenarios in which team‐related resources may improve organizational outcomes. Thus, the RBV gives a fine vantage point for examining the interaction between organizational and team‐level characteristics to forecast whether team I‐deals may contribute internationally to export SMEs.…”
Section: Introductionmentioning
confidence: 99%